Anaphylaxis: Lessons from mouse models - Finkelman, Fred D. (Journal of allergy and clinical immunology, 2007)
Studies with mouse models demonstrate 2 pathways of systemic anaphylaxis: a classic pathway mediated by IgE, FcɛRI, mast cells, histamine, and platelet-activating factor (PAF) and an alternative pathway mediated by IgG, FcγRIII, macrophages, and PAF. The former pathway requires much less antigen and antibody than the latter. This is modified, however, by IgG antibodies that prevent IgE-mediated anaphylaxis by intercepting antigen before it binds to mast cell–associated IgE. Consequently, IgG antibodies block systemic anaphylaxis induced by small quantities of antigen but mediate systemic anaphylaxis induced by larger quantities. The importance of the alternative pathway in human subjects is unknown, but human IgG, IgG receptors, macrophages, mediators, and mediator receptors have appropriate properties to support this pathway if sufficient IgG and antigen are present. The severity of systemic anaphylaxis is increased by nitric oxide produced by the enzyme endothelial nitric oxide synthase and by the cytokines IL-4 and IL-13 and decreased by endogenous β-adrenergic stimulation and receptors that contain ITIM that bind tyrosine phosphatases. Anaphylaxis is also suppressed by other receptors and ion channels that function through distinct mechanisms. Unlike systemic anaphylaxis, intestinal anaphylaxis (allergic diarrhea) is almost totally IgE and mast cell dependent and is mediated predominantly by PAF and serotonin. Some potent food allergens, including peanuts and tree nuts, can directly enhance anaphylaxis by stimulating an anaphylactoid response through the innate immune system. Results of these studies suggest novel prophylactic agents, including nonstimulatory anti-IgE mAbs, IL-4 receptor antagonists, PAF antagonists, and agents that cross-link FcɛRI or FcγRIII to an ITIM–containing inhibitory receptor.